Presence of tracheal bronchus in children undergoing flexible bronchoscopy. Issue 7 (July 2015) - Ruchonnet-Metrailler, Isabelle; Abou Taam, Rola; de Blic, Jacques
Summary: Background and objectives: Tracheal bronchus (TB) is a rare congenital malformation of the lung tree with a bronchus originating from the trachea. Only a small number of publications have analyzed the frequency and diagnostic procedure of TB in children, based on a restricted sample of patients. In the present study, we analyze and discuss new aspects of prevalence, clinical presentation and associated malformations of TB based on a large pediatric cohort. Methods: Data from 5970 children having a flexible bronchoscopy for investigation of respiratory symptoms were selected. We analyzed the anesthesic management, the presence of associated malformations, and all tracheobronchial anomalies observed during the endoscopic procedure. Results: Fifty-seven cases of tracheal bronchus were identified (0.9%). In the majority of them, tracheal bronchus was a fortuitous discovery without clear clinical relevance. Statistical analysis revealed that the majority of TB originated from the middle and lower one third of the trachea (56%). 61.5% of patients had associated anomalies such as syndromic association (21%), cardiac malformations (19.2%) or tracheal stenosis (14%). Only 38.5% of children had no associated anomalies. Conclusions: Tracheal bronchus is a rare morphological anomaly of the tracheobronchial tree. Most often TB is associated with other birth defects such as another tracheo-bronchial tree malformation, vascular abnormality, congenital heart malformation or in the context of a syndromic pattern. A relationship between respiratory symptoms and the presence of TB is very rare and selective treatment is infrequent.